Insights into northern leaf blight disease : investigating the Exserohilum turcicum-Sorghum bicolor interaction - Crampton, Bridget Genevieve (University of Pretoria, 2022)
Thesis (PhD (Biotechnology))--University of Pretoria, 2022.